Analysis of Teamwork and Work–Life Balance in Enhancing the Motivation of Part-Time Working Students - Arsy Sabilla; Aulia Putri Kinasih; Regina Christy (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : In recent years, the number of part-time working students has increased significantly, resulting in the need to understand factors influencing their motivation. Balancing academic responsibilities with part-time work often leads to stress and decreased productivity. Therefore, teamwork and work–life balance are believed to play essential roles in enhancing motivation among these students. Objective : This study aims to analyze the influence of teamwork and work– life balance on the motivation levels of part-time working students. Research Methods/ Implementation Methods : This quantitative research employed a survey distributed to 100 part-time working students using a structured questionnaire. The collected data were analyzed through validity and reliability tests, followed by t-tests and F-tests to determine the effect and significance of each variable. Results : The results indicated that both teamwork and work–life balance have a positive and significant impact on student motivation. Teamwork improved collaborative learning and emotional support, while work–life balance reduced stress and increased focus on both work and academic goals. Conclusion/Lesson Learned : The study concludes that teamwork and maintaining a healthy work life balance are key factors in enhancing motivation among part-time working students. Educational institutions and employers should develop supportive environments that encourage collaboration and flexible scheduling to sustain student motivation.